PEDAGOGIC FUNCTIONS OF TEACHERSâ€™ CODE-SWITCHING IN GARUDA BILINGUAL KINDERGARTEN - Pinatih, I Gusti Ayu Arya Satyani (Lingua Scientia, 2019)
EvenÂ thoughÂ codeswitchingÂ hasÂ becomeÂ aÂ naturalÂ phenomenonÂ andÂ occurredÂ inÂ regularÂ basisÂ duringÂ the teachingÂ  andÂ  learningÂ  processÂ  inÂ  bilingualÂ  classroom,Â  theÂ  pedagogicÂ  analysisÂ  ofÂ  theÂ  occurringÂ  switches shouldÂ  beÂ  takenÂ  intoÂ  accountÂ  toÂ  figureÂ  outÂ  whetherÂ  theÂ  switchesÂ  areÂ  indeedÂ  aÂ  pedagogicÂ  toolÂ  usedÂ  by bilingualÂ  teachersÂ  forÂ  theÂ  comprehensionÂ  andÂ  achievementÂ  ofÂ  theÂ  lessonÂ  content.Â  Therefore,Â  the objectiveÂ  ofÂ  thisÂ  studyÂ  isÂ  toÂ  figureÂ  outÂ  theÂ  functionsÂ  ofÂ  teachersâ€™Â  codeâ€switchingÂ  duringÂ  classroom teachingÂ  andÂ  learningÂ  processÂ  inÂ  GarudaÂ  BilingualÂ  Kindergarten.Â  ThisÂ  studyÂ  wasÂ  conductedÂ  usingÂ  a descriptiveÂ  qualitativeÂ  design.Â  TheÂ  dataÂ  wereÂ  collectedÂ  throughÂ  classroomÂ  observationÂ  andÂ  recordings. TheÂ  obtainedÂ  dataÂ  wereÂ  analyzedÂ  basedÂ  onÂ  theÂ  codingÂ  categoriesÂ  ofÂ  pedagogicÂ  functionÂ  theory.Â  The findingsÂ  indicateÂ  thatÂ  theÂ  functionsÂ  ofÂ  theÂ  occurringÂ  codeâ€switchingÂ  are:Â  1)Â  instructionalÂ  forÂ  content acquisition,Â  2)Â  reformulationÂ  of content,Â  3)Â  facilitation,Â  andÂ  4)Â  habitual.Â  TheÂ  resultÂ  ofÂ  thisÂ  studyÂ  is expectedÂ  toÂ  beÂ  usefulÂ  especiallyÂ  forÂ  teachersÂ  toÂ  knowÂ  theÂ  roleÂ  ofÂ  codeâ€switchingÂ  inÂ  supportingÂ  the emergentÂ  bilingualsÂ  duringÂ  classroomÂ  teachingÂ  and learningÂ  processÂ  asÂ  wellÂ  asÂ  toÂ  helpÂ  teachersÂ  planÂ  a moreÂ effectiveÂ languageÂ strategy.